Effect of Nitrogen and Seeding Rate on β-Glucan, Protein, and Grain Yield of Naked Food Barley in No-Till Cropping Systems in the Palouse Region of the Pacific Northwest - Habiyaremye, Cedric; Schroeder, Kurtis L.; Reganold, John P.; White, David; Packer, Daniel; Murphy, Kevin M. (Frontiers in Sustainable Food Systems, 2021)
Barley (Hordeum vulgare L.) has a storied history as a food crop, and it has long been a dietary staple of peoples in temperate climates. Contemporary research studies have focused mostly on hulled barley for malt and animal feed. As such, nitrogen (N) and seeding rate agronomic data for naked food barley are lacking. In this study, we evaluated the effects of N on ß-glucan and protein content, and N and seeding rate on phenotypic characteristics of naked food barley, including grain yield, emergence, plant height, days to heading, days to maturity, test weight, percent plump kernels, and percent thin kernels. Experiments were conducted at two no-till farms, located in Almota, WA, and Genesee, ID, in the Palouse region of the Pacific Northwest from 2016 to 2018. The experiment comprised two varieties (‘Havener’ and ‘Julie’), employed N rates of 0, 62, 95, 129, and 162 kg ha-1, and seeding rates of 250, 310, and 375 seeds/m2. Increased N fertilization rate was shown to significantly increase all response variables, except β-glucan content of the variety Julie, days to heading, test weight, and percent plump and thin kernels. Increased N fertilization resulted in higher mean grain yield of Havener and Julie in both Almota and Genesee up to 95 kg ha-1. Havener had higher yields (3,908 kg ha-1) than Julie (3,099 kg ha-1) across locations and years. Julie had higher β-glucan (8.2%) and protein (12.6%) content compared to Havener (β-glucan=6.6%; protein=9.1%). Our results indicate that β-glucan content is associated with genotype, environmental, and agronomic factors in dryland cropping systems of the Palouse.